PERENCANAAN PEMBANGUNAN BERBASIS PERTANIAN TANAMAN PANGAN DALAM UPAYA PENANGGULANGAN MASALAH KEMISKINAN - Arifien, Moch.; Fafurida, Fafurida; Noekent, Vitradesie (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2012)
The main objective of this study is planning for development the agricultural sector, especially food plants in order to improve the local economy. The steps taken is to examine the performance of the agricultural sector in the district, identify potential food plants to be developed in each sub district, construct a hierarchy of centers of social services and economic development, planning the development of agriculture food plants in the district, then describe it in a planning map. The research was conducted in the district Wonosobo. Analysis of the research carried out by using Shift Share analysis, Location Quotient (LQ), and analysis skalogram. The results showed that the highest productivity in agriculture in the district is Wonosobo vegetable plants. Types of plants that can be developed are food plants that have competitive and comparative advantage.